2009
DOI: 10.1073/pnas.0804273106
|View full text |Cite
|
Sign up to set email alerts
|

Gliomas induce and exploit microglial MT1-MMP expression for tumor expansion

Abstract: for highly malignant gliomas (World Health Organization grade III and IV) there is no successful treatment; patients have an average survival time of approximately 1 y after diagnosis. Glioma cells are highly invasive and infiltrate normal brain tissue, and as a result, surgical resection is always incomplete. Degradation of ECM by membrane-bound and secreted metalloproteases facilitates glioma invasion. In particular, the membrane-bound metalloproteases are pivotal for tumor invasion as they very efficiently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
328
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(354 citation statements)
references
References 37 publications
14
328
3
4
Order By: Relevance
“…The up-regulation of MT1-MMP was mediated by toll-like receptor signaling since it was abolished in a mouse line with deletion of a molecule essential for most toll-like receptor signaling. Glioma growth was also strongly attenuated in the MyD88-deficient mouse model (Markovic et al, 2009). The importance of microglia for glioma growth was further substantiated by studying animals in which microglia were depleted.…”
Section: Microglia Promote Glioma Migration and Tumor Growthmentioning
confidence: 97%
See 1 more Smart Citation
“…The up-regulation of MT1-MMP was mediated by toll-like receptor signaling since it was abolished in a mouse line with deletion of a molecule essential for most toll-like receptor signaling. Glioma growth was also strongly attenuated in the MyD88-deficient mouse model (Markovic et al, 2009). The importance of microglia for glioma growth was further substantiated by studying animals in which microglia were depleted.…”
Section: Microglia Promote Glioma Migration and Tumor Growthmentioning
confidence: 97%
“…To restrict the effect of ganciclovir on the intrinsic microglial population, the mice were irradiated before bone marrow transplanted with wild-type monocytes. The ganciclovir treatment led to a considerable depletion of microglia and to an 80% reduction in glioma volume (Markovic et al, 2009). Using the similar mouse model, Galarneau et al (2007) injected ganciclovir i.p.…”
Section: Microglia Promote Glioma Migration and Tumor Growthmentioning
confidence: 99%
“…Results from in vitro studies support the idea that microglia can promote tumor invasion and growth (Bettinger et al, 2002;Markovic et al, 2005). Perhaps the most convincing evidence of the importance of microglia to glioma formation is from in vivo studies that have shown that tumor cell growth is inhibited in microglia-deficient glioma mouse models (Daginakatte and Gutmann, 2007;Markovic et al, 2009). These findings suggest that therapies that target glioma-associated microglia may be promising antitumor agents.…”
Section: Microgliamentioning
confidence: 84%
“…In addition, brain tumor stem-like cells can act on microglia and induce the secretion of cytokines (for example, TGFb1, MIC-1, sCSF-1) that promote an immunosuppressive phenotype (Wu et al, 2010). In addition, it has been shown that soluble factors secreted by tumor cells can cause the upregulation of matrix metalloproteinase-14 (MMP-14) expression in microglia (Markovic et al, 2009). MMP-14 can activate inactive matrix metalloprotease-2 secreted by glioma cells and lead to the break down of the extracellular matrix.…”
Section: Microgliamentioning
confidence: 99%
“…It is postulated that glia contribute to this inflammatory process by producing cytokines including IL-1β and TNF-α [14]. Glial cells may also affect metastatic growth within the brain [311,312] and be used by tumor cells to support its progression and invasion [313,314].…”
Section: Current Research On Antidepressant Use and Cns Metastasismentioning
confidence: 99%